AKUNTANSI MANAJEMEN DALAM PRESPEKTIF STRATEGI KEUNGGULAN BERSAING - Fahrudin A, Ahmad (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2010)
Dynamics business makes strategic outlook as an important paradigm in management accounting. Contemporary management accounting is ineligible to occupy only the calculation of costs and decision-making regardless of environmental factors that move fast. By combining competitive strategy,  management accounting tools are expected  to support the role of strategic choice taken by firm. This article discusses how far management accounting can play an active role to create a competitive advantage in the competitive business. Keyword: Akutansi  manajemen,  strategi, otomatisasi, keunggulan.